Application of CIRC Learning Model to Improve The Ability to Read the Understanding of Narrative Discourse of Grade V Elementary School Students - Nurfitria; Hartati, Tatat (International Conference on Elementary Education, 2022)
This research aims to find out the ability to read the understanding of narrative discourse after applying the cooperative integrated reading and composition (CIRC) learning model to students of class V SDN Ciporeat I sub-district of Ujungberung city of Bandung. This type of research is class action research. The subject of this study was a student of class V SDN Ciporeat I which amounted to 35 students. Learning outcome data reading the understanding of student narrative discourse is collected with test instruments in the form of descriptions. The data obtained is analyzed using quantitative descriptive statistical analysis techniques. Based on the results of the analysis of data on cycle I obtained an average of 68.06 with sufficient categories (68.06%), in cycle II obtained an average of 73.02 with medium category (73.02%) and in cycle III obtained an average of 85.06 with good category (85.06%) There was an increase from cycle I to cycle II by 4.96% and cycle II to cycle III by 12.04%. Thus it can be concluded that the completion of the cooperative integrated reading and composition (CIRC) learning model can improve the ability to read the understanding of the narrative discourse of students of class V SDN Ciporeat I sub-district of Ujungberung city of Bandung.